Trend Penelitian Computational Thinking pada Pembelajaran Sains: A Sytematic Review - Nurazizah, Siti; Maharani , Dwifta Fuji; Sari, Indah Juwita (Pimpinan Cabang Muhammadiyah Kramat Jati, 2025)
This study aims to examine the trend of computational thinking (CT) implementation in science learning through a systematic literature review (SLR) approach. The method used is descriptive qualitative by analyzing 11 articles published between 2021 and 2025 and obtained from the ERIC database. The results of the review show that CT has been widely applied at various levels of education, especially at the Elementary School (SD) and High School (SMA) levels, as well as in subjects such as physics, chemistry, and science. The learning approaches that are often used include STEM, STEAM, Design-Based Research, and learning models based on modeling and authentic investigation. CT has been proven effective in improving critical thinking skills, understanding of science concepts, and student learning outcomes. These findings indicate that the integration of CT in science learning has great potential to support 21st century science and technology literacy. This study makes an important contribution in providing guidance for Education and researchers to design innovative learning strategies that are relevant to today's needs.